SELECTION OF COINCIDENCE ELECTRON-PROTON EVENTS IN NUCLEI INTERACTION - Martiryan, D.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
The main goal of this analysis is to study momentum (or kinetic energy) distribution of the backward going protons using data from CLAS EG2 experiment at Jefferson Lab. In this experiment scattering of a 5.014 GeV electron beam off various nucleus targets, ranging from deuterium to lead, have been recorded. The analysis includes selection of events in the reaction $ A(e, e^{′}, P_{back}) X $, where $ P_{back} $ is a proton scattered above 90° either in the lab coordinate frame or with respect to the direction of the interacting virtual photon, then performing required corrections and studying the protons momentum distribution as a function of energy transfer. In this paper identification of electron-proton events is presented.
Keywords: backward going protons; CLAS EG2; coincidence electron-proton events